The Belorussian IT sector as a panacea for the shortage of specialists in the labour market of selected post-communist countries - Zofia Gródek-Szostak; Karolina Kotulewicz-Wisińska; Rafał Lisiakiewicz; Wojciech Zysk (International Entrepreneurship Review, 2023)
Objective: The objective of the article is to analyse the status of IT specialists in the labour market of selected post-communist countries: Belarus, Poland, Lithuania, Latvia, Estonia, and Ukraine.